REKONSEPTUALISASI PEMBERHENTIAN PRESIDEN DAN/ATAU WAKIL PRESIDEN DALAM MASA JABATANNYA DI INDONESIA - Fitria Esfandiari (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2018)
Reconceptualization can be interpreted as redefining the idea of the dismissal of the President and/or Vice President during his tenure in Indonesia. The fundamental problem with the dismissal of the President and /or Vice-President is in two things, first, related to the reasons, second, to procedures. This paper tries to compare the dismissal of the President and /or Vice President before and after the amendment to the 1945 Constitution. The shifting of the parliamentary system to strengthening presidential systems has legal implications in the constitutional system. The research method used is a normative research method with a statute approach. The results of the study show that in term of the dismissal of the President and / or Vice President based on history in Indonesia, they are more dominated by political aspects than purely violations of law. This is contradicted by the principle of legal certainty and the principle of legality. The Constitutional Court as a state institution that examines and decides the violation of the law of a President and / or Vice President has historically been formed as a manifestation of the principles of the rule of law, namely a free and impartial judiciary. Keywords: Reconceptualization, Presidential System, Dismissal of President/Vice President